Economic Crises, Maternal and Infant Mortality, Low Birth Weight and Enrollment Rates: Evidence from Argentina's Downturns - Guillermo Cruces; Pablo Glüzman; Luis Felipe López Calva (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2011)
This study investigates the impact of recent crises in Argentina (including the severe downturn of 2001-2002) on health and education outcomes. The identification strategy relies on both the inter-temporal and the cross-provincial co-variation between changes in regional GDP and outcomes by province. These results indicate significant and substantial effects of aggregate fluctuations on maternal and infant mortality and low birth weight, with countercyclical though not significant patterns for enrollment rates. Finally, provincial public expenditures on health and education are correlated with the incidence of low birth weight and school enrollment for teenagers, with worsening results associated with GDP declines. – crisis ; infant mortality ; maternal mortality ; low birth weight ; poverty ; Argentina – – Este estudio investiga el impacto de las recientes crisis en Argentina (incluyendo la grave recesión de 2001-2002) en la salud y la educación. La estrategia de identificación se basa en la covarianza entre los cambios en el PIB regional y los resultados por provincia en términos intertemporales e interprovinciales. Estos resultados indican efectos significativos e importantes de las fluctuaciones agregadas en la mortalidad materna e infantil y en el bajo peso al nacer, así como un patrón contracíclico aunque no significativo para las tasas de matrícula. Finalmente, el gasto público provincial en salud y educación se correlacionan con la incidencia del bajo peso al nacer y la matriculación escolar de los adolescentes, con peores resultados ante una disminución del PIB.
Keywords: 330; crisis; infant mortality; maternal mortality; low birth weight; poverty; Argentina; Wirtschaftskrise; Nationaleinkommen; Sterblichkeit; Kindersterblichkeit; Armut; Argentinien